Antioxidant Properties of Some Herbal Teas (Green tea, Senna, Corn Silk, Rosemary) Brewed at Different Temperatures - Ceyhun Kılıç; Zehra Can; Ayşenur Yılmaz; Sibel Yıldız; Hülya Turna (International Journal of Secondary Metabolite)
Some non-wood forest products are brewed and consumed as tea. Among the reasons for the consumption of herbal tea, digestive problems are located in the first row. Antioxidants help to human body for arranging digestive and immune system. Herbal tea is brewed in various ways such as boiling at different durations or waiting in hot water at different temperatures etc. Type of brewing can affect to bioactive properties of herbal tea. In this study, it was investigated the bioactive properties (total phenolic content, total flavonoid content, condensed tannin content and antioxidant properties) of some herbals brewed (Green tea / Camellia sinensis., senna / Cassia sp., corn silk / Zea mays, rosemary / Rosmarinus officinalis) at different temperature.  These herbs were brewed for 10 minutes at 60oC, 80 oC and 100 oC temperatures. After cooling, total phenolic, flavonoid content, total condensed tannin content and antioxidant properties of these herbs were determined. Consistently, the highest results were found in the tea brewed at 100oC. The highest total flavonoid (0.305 ± 0.005 mg QE/g) and ferric reducing ability (670.150 ± 2.121 µmol FeSO47H2O/g) was in Rosmarinus officinalis. The highest condensed tannin (9.443 ± 0.524 mg CE/g) and the highest total phenolic content (4.872 ± 0.005 mg GAE/g) was in Camellia sinensis and Cassia sp., respectively.